Perbandingan Sejarah Gereja Ortodoks dan Katolik: Asal-usul dan Perkembangannya - Wau, Sofiana Desraini; Aruan, Tiopan; Batawi, Adrians (Jurnal Teologi dan Pelayanan Kerusso, 2025)
This article analyzes and compares the history of the Orthodox and Catholic Churches, focusing on the historical background, theological developments, and the social impact of the Great Schism in the 11th century. The research employs a comparative approach to analyze the theological, administrative, and cultural differences that led to the division between the two churches. The findings of this study indicate that although the Orthodox and Catholic Churches share common roots in Christian tradition, key theological differences, such as the Filioque doctrine and the authority of the Pope, have shaped two distinct church identities, each evolving in different social and political contexts. This analysis also reveals the long-term impact of the schism on Christian communities worldwide.